SOURCE TO SINK STUDY AT CONTINENT-SCALE (AFRICA): MANTLEDYNAMICS CONTROLS AND IMPLICATIONS FOR THE SEDIMENTROUTING SYSTEM - (:unkn) unknown (My University, 2017)
A source to sink approach was performed at the scale of a continent – African the frame of theTopoAfrica project, with three main objectives (1) the characterization of the relative importance ofdeformation (uplift) and climate (precipitation) (2) the quantification of the deformation, its nature and causes,(3) the effect of those deformations on the past African topography and on the sediment routing system. Wemainly focused on Western, Central and Austral Africa, characterized by anorogenic relief (plains andplateaus) record of long (several 100 km) to very long (several 1000 km) wavelength deformations,respectively of lithospheric and mantle origin.The sink measurement was based on the seismic stratigraphic analysis of numerous regional seismiclines (from the upstream part of the margin to the abyssal plain) merge of industrial and academic data,calibrated in ages and lithologies on reevaluated wells to get the best possible ages. Volumes measuredbetween successive time-lines, were compacted for a comparison with solid eroded volumes. Uncertaintieswere calculated (including ages, time-depth conversion law, porosities...) using the Volume Estimatorsoftware.The source study was performed using dated stepped planation surfaces (etchplains and pediplains) keymorphological features of Africa mappable at catchments-scale. During Late Paleocene to Middle Eocenetimes, Africa experienced a very hot and very humid climate leading to the formation of an African-scaleweathering surface (etchplain) known as the African Surface. This surface today deformed and preserved aslarge plains, domes or plateaus, can be used as (1) a marker of the very long wavelength deformations and (2)a reference level to measure eroded volumes since 40 Ma. Some other younger planation surfaces were alsomapped of (1) Early Oligocene and (2) Late Miocene ages.(1) Deformation (uplift) is the dominant control of the sediment budget. Climate (precipitation) changesonly enhance or inhibit
Keywords: African Research